Alloying effects on graphite spacing in gray iron. (2nd September 2016) - Rivera, Elis A.; Catalina, Adrian; Genau, Amber L.
Abstract : Even with decades of study, the complex development of solidification microstructures in cast iron is incompletely understood. In order to observe the effect of ternary and quaternary alloying additions on the solidification behaviour and graphite spacing of gray iron, directional solidification in a Bridgman furnace was used to carefully control solidification conditions. Specifically, alloys with industrially relevant amounts of silicon and manganese were studied. Average spacings for five compositions, containing varied amounts of Si and Mn, and velocities from 0.5 to 10 μm/s are reported. A critical velocity of around 1 μm/s was observed, above which the graphite structure loses directionality and austenite dendrites appear. Spacing measurements are compared to historical data and a new model, highlighting the importance of sulphur in determining spacing. Spacing measurements obtained in the traditional way were compared to results obtained using a recently developed automated MATLAB algorithm. The automated results compare favourably with traditional manual measurements and will allow for more robust measurement of eutectic spacing in a variety of systems where the spacing is highly irregular.